The effects of patents on the relationship between R&D activities and business management performance: Focus on South Korean venture companies - Seunghoo Jin; Daeyu Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Today, innovation is achieved by challenging the existing paradigm through cross-field collaboration, and R&D innovation plays a particularly crucial role. This study analyzed the effects of R&D innovation activities on business management performance in South Korea and examined the role that patents play in various R&D innovation activities. Panel regression and moderating effect analyses were conducted on small- and medium-sized venture enterprises that undertook new technology projects over five years (2015-2019). The results showed that R&D innovation activities had a significantly positive effect on both revenue, an indicator of business growth, and operating profit, an indicator of profitability. This implies that such activities play a positive role in management activities. Thus, enterprises should consider R&D innovation activities from a business growth strategy perspective. Additionally, the analysis showed that a firm's capacity to hold patents on R&D innovation activities has a positive moderating effect on business management performance. This study is significant, as it reveals the cause-and-effect relationship between R&D innovation actives and business management performance as well as the role of various types of innovation. The results could help enterprises to seamlessly implement innovation activities in the future.
Keywords: 650; business performance; panel data analysis; patents; R&D activities